Prioritas Pemeliharaan Jalan Kabupaten Berdasarkan Ketersediaan Alokasi Anggaran - Dadan Yuda Prayoga; Herman Herman; Ida Farida; Mirza Fathir; Greece Maria Lawalata (Jurnal Konstruksi, 2023)
Road infrastructure is one of the most strategic transportation infrastructure facilities. This is supported by road stability which is supported by road maintenance and repairs. Handling road repairs cannot be separated from funding from the budget of each region, especially in the district. Budget limitations affect road repairs, so there needs to be priority handling. The aim of the research is to determine the criteria that are the basis for prioritizing road maintenance and to develop a priority order for district road maintenance based on the availability of budget allocations in Banyuresmi District, Garut Regency. The research methodology uses a descriptive evaluative method, analyzed using the Analytical Hierarchy Process. The results of respondents' assessments of road maintenance handling show that the priority criteria consisting of the type of road damage factor have an influence of 31.9%; policy factors influence 31.7%; traffic condition factors influence 23%; and the service condition factor has an influence of 13%. The priority order for handling Regency road maintenance is based on the availability of budget allocations in Banyuresmi District, Garut Regency, for the Pasirmuncang - Cipicung, Tanjung - Maleer, Cipicung - Wanaraja, Cibudug - Cipicung, Bojongsalam - Menger, Jager - Jolok/Cipicung, and Warungpeuteuy - Kiaralawang roads.